Formulation, performance evaluation and prediction of bio- lubricant for journal bearings / Diyar I. Ahmed - Ahmed, Diyar I. (Institute of Graduate Studies, UiTM, 2014)
This thesis is concerning about hydrodynamic lubrication in journal bearing. The research covers three primary areas: the formulation of an alternative biodegradable bio-lubricant using renewable resources; the performance evaluation of the formulated oil through a true-scale versatile journal bearing test rig; and the modeling and prediction the behavior of bio-lubricant around the bearing circumference. The first part of the research is focused upon the formulation of an environmentally-friendly lubricant using vegetable oil with various composition of petroleum base stock. The physico-chemical and tribochemical properties of the formulated oil have been analyzed using multiple standards apparatuses. This study provides valuable data to conform an ISO VG 68 hydraulic industrial lubricant by blending 52.70 % (wt) soybean oil, 40.55 % (wt) mineral oil, and 6.75 (%) additive packages. The experimental results clearly demonstrated that the formulated green lubricant was far more efficient than the synthetic lubricant in terms of friction coefficient, wear rates, wear volume loss and worn surface morphologies. However, the green lubricant failed to outperform conventional lubricant with respect to degradation test and wear scar diameter performance.